Advancing Care for Family Caregivers of persons with dementia through caregiver and community partnerships - White, Carole L. (Res Involv Engagem, 2018)
BACKGROUND: There are currently 15 million Americans who provide over 80% of the care required by their family members with Alzheimer’s disease and other dementias. Yet care for caregivers continues to be fragmented and few evidence-based interventions have been translated into routine clinical care and therefore remain inaccessible to most family caregivers. To address this gap, the Caring for the Caregiver program is being developed at UT Health San Antonio, School of Nursing to improve support services and health outcomes for family caregivers. Our purpose is to describe the engagement process undertaken to assess caregiver and community needs and how findings are informing program development. METHODS: We are using a model of public engagement that consists of communication of information, collection of information from stakeholders, and collaboration where stakeholders are partners in an exchange of information to guide program activities. An assessment of the community was undertaken to identify resources/services for family caregivers. Subsequently, stakeholders were invited to a community-academic forum to discuss strategies to build on existing strengths for family caregiving and to identify gaps in care. Detailed notes were taken and all discussions were recorded and transcribed for analysis. Data were analyzed using thematic content analysis. RESULTS: We conducted site visits with 15 community agencies, interviewed 13 family caregivers, and attended community events including support groups and health and senior fairs. Fifty-three diverse stakeholders attended the community-academic forum. Participants identified existing assets within our community to support family caregivers. Consistent among groups was the need to increase awareness in our community about family caregivers. Themes identified from the discussion were: making the invisible visible, you don’t know what you don’t know, learning too late, and anticipating and preparing for the future. CONCLUSIONS: Incorporating caregiver and community stakeholders was critical to ensure that the priorities of our community are addressed in a culturally responsive accessible program for family caregivers. The forum served as important mechanism to partner with the community and will be an annual event where we can continue to work with our stakeholders around needs for practice, education, and research.